Self-reported sleep in late pregnancy in relation to birth size and fetal distress: the E Moe, Māmā prospective cohort study. Issue 10 (5th October 2015) - Howe, Laura D; Signal, T Leigh; Paine, Sarah-Jane; Sweeney, Bronwyn; Priston, Monique; Muller, Diane; Lee, Kathy; Huthwaite, Mark; Gander, Philippa
Abstract : Objectives: To explore associations between features of sleep during pregnancy and adverse outcomes for the infant. Setting: E Moe, Māmā is a cohort study in Aotearoa/New Zealand that investigates self-reported sleep and maternal health in late pregnancy and the postpartum period. Participants: Women (N=633; 194 Māori) reported detailed information on their sleep duration, quality, disturbances, disorders (snoring, breathing pauses, twitching legs, restless legs) and daytime sleepiness between 35 and 37 weeks gestation. Outcome measures: Birthweight and fetal distress during labour were extracted from medical records. Associations between each sleep variable and small or large for gestational age (SGA/LGA) using customised birthweight centile or fetal distress were estimated using multinomial/logistic regression, controlling for potential confounders. Secondary analyses considered differences in associations between Māori and non-Māori women. Results: There was some indication that breathing pauses (a measure of sleep apnoea) were associated with both SGA (OR 2.8, 95% CI 0.9 to 9.0, p=0.08) and LGA (OR 2.0, 95% CI 0.7 to 5.7, p=0.20), with the association for LGA being stronger when only pregnancy-onset breathing pauses were considered (OR 3.5, 95% CI 1.3 to 9.6, p=0.01). There was also some evidence that pregnancy-onset leg twitching (OR 3.3, 95% CI 1.1 to 10.0, p=0.03) and frequent sleep disturbance due to feeling too hot or too cold (OR 1.7, 95% CI 0.9 to 3.6, p=0.13) were associated with higher risk of fetal distress. Other sleep measures, including snoring, were not associated with SGA, LGA or fetal distress. Many of the associations we observed were considerably stronger in Māori compared with non-Māori women. Conclusions: We did not find evidence of previously reported associations between snoring and SGA. Our findings tentatively suggest that self-reported breathing pauses and leg twitching in late pregnancy are associated with infant outcomes, and highlight ethnic inequalities.